2017
DOI: 10.1080/09513590.2017.1410785
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of administration of 25-hydroxyvitamin D supplement on serum anti-mullerian hormone (AMH) levels in infertile women

Abstract: The aim of the study was to evaluate the effects of administration of 25-hydroxyvitamin D [25(OH) D] on serum antimullerian hormone (AMH) levels in infertile women. The study was performed as a non-randomized clinical trial on 30 infertile women who had low serum level of both 25(OH) D and anti-mullerian hormone. Vitamin D was prescribed 50,000 IU weekly for up to three months for all eligible participants. Serum levels of both 25(OH) D and AMH have increased significantly after treatment with 25(OH) D. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In a study of 30 infertile Iranian women >35 yo with regular cycles but diminished ovarian reserves (as defined by AMH < 0.7 ng/mL) and vitamin D deficiencies or insufficiencies (levels <30 ng/mL), Naderi et al similarly reported a significant increase in serum AMH levels (from 0.39 ± 0.26 to 0.92 ± 0.62 ng/mL, p < 0.000) following three months of 50,000 IU oral vitamin D3 supplementations. In addition, there was a significant positive correlation between the serum levels of 25OH-D posttreatment and AMH levels, with mean AMH levels after treatment being higher in women with sufficient 25OH-D vs. women with insufficient 25OH-D (1.048 ± 0.644 vs. 0.513 ± 0.284 ng/mL ( p = 0.043) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 30 infertile Iranian women >35 yo with regular cycles but diminished ovarian reserves (as defined by AMH < 0.7 ng/mL) and vitamin D deficiencies or insufficiencies (levels <30 ng/mL), Naderi et al similarly reported a significant increase in serum AMH levels (from 0.39 ± 0.26 to 0.92 ± 0.62 ng/mL, p < 0.000) following three months of 50,000 IU oral vitamin D3 supplementations. In addition, there was a significant positive correlation between the serum levels of 25OH-D posttreatment and AMH levels, with mean AMH levels after treatment being higher in women with sufficient 25OH-D vs. women with insufficient 25OH-D (1.048 ± 0.644 vs. 0.513 ± 0.284 ng/mL ( p = 0.043) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the six interventional studies included in this systematic review, three out of six studies reported an increase in serum AMH levels in non-PCOS vitamin D-deficient women following both acute [62] and long-term [61,63] vitamin D supplementations (Table 2). In contrast to these three studies, Cappy et al found no changes in serum AMH following vitamin D supplementations in either PCOS or non-PCOS women.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heavy metals such as cadmium are increased in aquatic environments through industrial processes and fertilizers and can be introduced to humans through fish [ 13 ]. Moreover, fish is also a source of other compounds, such as vitamin D, which is associated with serum AMH [ 14 ]. Some participants had missing data for a given variable.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro studies demonstrated that the AMH gene is upregulated by vitamin D via functional vitamin D response elements that bind the vitamin D receptor (VDR) [6]. There are multiple reports regarding the relationship between AMH and vitamin D and the impact of vitamin D supplementation on AMH levels [32, 13, 16]. When analyzing the available literature, it is clear that most of the studies revealed that supplementation of vitamin D to women with low AMH levels leads to an increase in these levels, thus improving reproductive outcomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a vast majority of studies, a significant correlation was observed between AMH and vitamin D levels. Naderi and coworkers suggested that vitamin D supplementation leads to increased serum AMH levels [16]. Slightly different results were obtained by Irani and coworkers who showed that administration of vitamin D in women with PCOS may reduce the AMH levels [17].…”
Section: Introductionmentioning
confidence: 99%